A three-dimensional framework for multi-tier sustainable supply chain management. Issue 6 (26th October 2018) - Sauer, Philipp C.; Seuring, Stefan
Abstract : Purpose: This study aims to investigate the under-researched role of the sub-supplier's direct environment in achieving compliance with multi-tier sustainable supply chain management (MT-SSCM) objectives. Design/methodology/approach: Building on conceptual research, this study aims to generalize the characteristics of multi-tier supply chains in light of institutional theory and supply chain (SC) uncertainty to enhance the understanding of their complex interrelationship. Findings: A three-dimensional framework is built around the supply and demand uncertainty as well as the pressures for sustainability exerted by the supplier's direct environment to propose ideal constellations for the application of MT-SSCM. Moreover, research directions and implications for the alteration of suboptimal constellations are developed. Practical implications: Incorporating the supplier's environment in the choice of MT-SSCM practices couples the sustainability priorities of the focal firm and the supplier. This enables a more complete picture of the sustainability objectives and sustainable development aims of the SC partners. Originality/value: On the basis of institutional theory, the study extends current MT-SSCM concepts by including the supplier's direct environment in the choice of ideal management practices in a particular SC setup. It provides a definition of a multi-tier SC as an institutional field and a number of research implications regarding MT-SSCM as well as generic SSCM. Moreover, the proposed framework helps SC managers to understand the complex interplay of the SC partners' sustainability aims and provides implications for choosing the most suitable MT-SSCM practices.